Minimum Contact Time of 1.25%, 2.5%, 5%, and 10% Benzoyl Peroxide for a Bactericidal Effect Against Cutibacterium acnes - Boonchaya P; Rojhirunsakool S; Kamanamool N; Khunkhet S; Yooyongsatit S; Udompataikul M; Taweechotipatr M (Dove Medical Press, 2022)
Punyanun Boonchaya,1 Salinee Rojhirunsakool,1 Nanticha Kamanamool,2 Saranya Khunkhet,1 Surasak Yooyongsatit,3 Montree Udompataikul,1 Malai Taweechotipatr3 1Department of Dermatology, Faculty of Medicine, Srinakharinwirot University, Bangkok, Thailand; 2Department of Preventive and Social Medicine, Srinakharinwirot University, Bangkok, Thailand; 3Department of Microbiology, Faculty of Medicine, Srinakharinwirot University, Bangkok, ThailandCorrespondence: Salinee Rojhirunsakool, Department of Dermatology, Faculty of Medicine, Srinakharinwirot University, 114 Sukhumvit 23, Wattana District, Bangkok, 10110, Thailand, Tel +66 894159665, Email salineer@g.swu.ac.thPurpose: Benzoyl peroxide (BPO) is an effective acne treatment and has been used as a cleanser and short contact therapy. However, data on the minimum contact time of BPO needed to kill Cutibacterium acnes are lacking. Thus, the aim of this study was to determine the minimum contact time of commonly used BPO concentrations for bactericidal effects on C. acnes.Materials and Methods: An in vitro experimental study of clinically isolated C. acnes was performed to determine the minimal inhibitory concentration (MIC) of BPO using the broth microdilution method. Subsequently, the minimum contact times of various concentrations of BPO were evaluated, and their bactericidal effects were assessed by the plate count method.Results: The median MIC of BPO was 9375 μg/mL, which did not significantly differ between antibiotic-resistant and nonresistant C. acnes. The minimum contact time of BPO with C. acnes was significantly different among the BPO concentrations. For bactericidal activity against all isolates, 1.25%, 2.5%, 5%, and 10% BPO required 60 min, 15 min, 30 sec, and 30 sec, respectively.Conclusion: BPO demonstrated bactericidal activity against both antibiotic-resistant and antibiotic-susceptible C. acnes. The in vitro contact time needed to kill C. acnes was almost immediate with 5% or more BPO, but ≤ 2.5% BPO required longer contact times for bactericidal effects.Keywords: acne, cleanser, short contact therapy, C. acnes, P. acnes, time killing